Ultrasonicated Lespedeza cuneata extract prevents TNF-α-induced early atherosclerosis in vitro and in vivo. Issue 4 (3rd April 2018) - Ha, Su Jeong; Lee, Jangho; Song, Kyung-Mo; Kim, Young Ho; Lee, Nam Hyouck; Kim, Young-Eon; Jung, Sung Keun
Abstract : This study evaluated the use of ultrasonication to extract Lespedeza cuneata as a potential nutraceutical for preventing vascular inflammation. Abstract : This study evaluated the use of ultrasonication to extract Lespedeza cuneata as a potential nutraceutical for preventing vascular inflammation. Ultrasonicated L. cuneata extract (ULCE) was prepared using 20% ethanol and 2 h of ultrasonication at room temperature, and its effects were investigated using relevant in vitro and in vivo models. ULCE suppressed tumor necrosis factor-alpha (TNF-α)-induced adhesion capacity, vascular cell adhesion protein 1 (VCAM-1) expression, and nuclear factor kappa-B (NF-κB) activity in human umbilical vein endothelial cells (HUVECs). ULCE also suppressed TNF-α-induced NF-κB signaling pathways and p65 translocation from the cytosol to the nucleus, as well as the mRNA expression of IL-1β, IL-6, and TNF-α in HUVECs. Oral administration of ULCE suppressed TNF-α-induced monocyte infiltration into the intima and VCAM-1 expression, as well as the IL-1β, IL-6, TNF-α, and monocyte chemoattractant protein-1 (MCP-1) mRNA expression in the main artery in mice. Among the compounds identified in the hydrolyzed ULCE, quercetin exhibited the strongest inhibitory effect against TNF-α-induced cell adhesion capacity. These results demonstrate that ULCE contains potent preventive factors against early atherosclerosis, which act by suppressing the NF-κB and VCAM-1 signaling axis.